Home range and habitat selection by the tropical screech-owl in a Brazilian savanna - Barros, Fabio M.; Motta-Junior, Jose C. (Raptor Research Foundation Inc, 2014)
The Tropical Screech-Owl (Megascops choliba) is a small nocturnal raptor that uses a large range of habitats throughout Brazil. Although it is one of the most abundant owls in the Neotropics, nothing has been published on its spatial ecology, and information on basic natural history is scarce. We followed four radio-tagged males to estimate home-range size and habitat selection in a savanna (cerrado) patch in southeastern Brazil. The mean (+/- SD) home-range size was 51.2 (26.9) ha using the 95% minimum convex polygon (MCP) method and 80.8 (40.2) ha using the 95% fixed kernel (FK) method. The mean (+/- SD) core area was 22.4 (8.8) ha (65% FK). During nocturnal activities, owls preferred semi-open (campo cerrado) and semi-closed (cerrado sensu stricto) habitats and avoided open habitats (campo sujo). Gallery forests and patches of invasive pines were preferred for roosting during the day. The variation in size of individual home ranges may be explained by individual's breeding status and habitat structure. Home-range sizes of Tropical Screech-Owls were generally similar to those of other screech-owls in North America, and the small differences in area requirements among species may be related to body mass and habitat structure.
Keywords: Tropical Screech-Owl; Megascops choliba; Brazil; cerrado; home range; spatial ecology; Strigiformes; telemetry